AB1149 A Simple Assessment of Psychological Distress in Rheumatoid Arthritis Patients Using Multidimensional Health Assessment Questionnaire (MDHAQ): A Validation Study of Psychological MDHAQ. (9th June 2015) - Yokogawa, N.; Kaneko, T.; Nagai, Y.; Nunokawa, T.; Sawaki, T.; Shiroto, K.; Shimada, K.; Sugii, S.
Abstract : Background: Multidimensional Health Assessment Questionnaire (MDHAQ) was designed to assess quality of life impairment including psychological distress in rheumatoid arthritis (RA) patients. In addition to ten questions dealing with the patient's physical activity (Q1-10), MDHAQ also includes the following three questions, which address the psychological state of the patient: "Get a good night's sleep?" (Q11), "Deal with feelings of anxiety or being nervous?" (Q12), and "Deal with feelings of depression or feeling blue?" (Q13) [1]. The utility of these questions in daily clinical practice has not been described. Objectives: To define psychological MDHAQ as the mean score of Q11-13 and to validate it in RA patients Methods: A previously validated Japanese version of MDHAQ was used in this study [2]. The validation of psychological MDHAQ included test-retest reliability (50 patients), content validity, and concurrent validity (348 patients). Hospital Anxiety and Depression Scale (HADS) was used as a comparator. Results: Mean (SD) age and disease duration of the validation study population were 65.2 (12.1) years and 11.4 (10.5) years, respectively. The proportion of possible cases with anxiety (HADS-A ≥8), depression (HADS-D ≥8), and either anxiety, or depression (HADS-A ≥8 or HADS-D ≥8) was 21.5%, 25.4%, and 35.5%, respectively. The test-retest reliability of Q11, Q12, Q13, and psychological MDHAQ was 0.730, 0.757, 0.708 and 0.788 (Spearman's rank correlation coefficient), respectively. The internal reliability of Q11, Q12, and Q13 was 0.930, 0.628, and 0.680 (Chronbach's α), respectively. The correlation between Q11 and 12, Q11 and 13, and Q12 and 13 was 0.503, 0.463, and 0.891 (Spearman's rank correlation coefficient), respectively. Psychological MDHAQ correlated with HADS while also showing a higher correlation with all patient-reported outcome measures (pain VAS, patient global VAS, HAQ, and RAPID3) than did HADS (Table 1 ). In screening for possible cases of anxiety, or depression, psychological MDHAQ ≥0.67 (total Q11-13 of ≥2) showed moderate agreement with HADS-A ≥8 or HADS-D ≥8 (kappa 0.441, p<0.0001). Conclusions: Psychological MDHAQ was found to be suitable for use in daily practice to assess psychological distress. References: Pincus T, et al. Arthritis Rheum 1999;42:2220-30. Yokogawa N, et al. Mod Rheumatol 2014; 26:1-6. Disclosure of Interest: None declared